Seasonal and interannual variability of planktonic microbes in a mesotidal coastal lagoon (Ria Formosa, SE Portugal): impact of climatic changes and local human influences - Barbosa, Ana B. (2012)
The Ria Formosa coastal lagoon is a multi-inlet mesotidal system, located along the south coast of Portugal. It is subjected to multiple anthropogenic influences and is situated in a region classified as very vulnerable to climate change. This study aimed to describe the seasonal and interannual variability of planktonic microbes in the lagoon, the driving forces underlying microbe variability, and the relative contribution of climate and local-human influences. Changes in anthropogenic activities or climatic processes affecting the Ria Formosa Lagoon were identified for the period 1967 to 2008 and linked to current knowledge on abiotic variables and planktonic microbes in the western subembayment of the lagoon. Phytoplankton and heterotrophic bacterioplankton at inner lagoon locations exhibited unimodal annual cycles with summer peaks, coupled to temperature and light availability, whereas phytoplankton at inlet areas displayed a bimodal annual cycle, probably more intensively controlled by nutrient availability. The effects of increased anthropogenic pressure, both on seasonal and interannual time scales, were evident only at sites close to major urban centers, probably due to the low water residence time inside the lagoon, and the relevance of physical variables (e.g., temperature and light) as drivers of the growth of planktonic microbes. Long-term climatic variability apparently reverberated into the lagoon’s water column, leading to a generalized and significant winter warming trend, and strong interannual changes in the concentration of inorganic nutrients, particularly during the autumn–winter period. Phytoplankton biomass showed a generalized interannual declining trend during autumn and winter. This decline may be eventually related to the winter warming tendency, through its stimulatory effect upon phytoplankton grazers, or to decreases in nutrient concentrations associated with reductions in the autumn freshwater inflow. Long-term changes during spring and summer were less coherent across lagoon stations, indicating that more site-specific processes were driving phytoplankton variability. Despite overall reduced freshwater flows into the lagoon, interannual freshwater flow variability apparently exerted an important control on the biomass of phytoplankton, particularly during periods of relatively high flow rates and low light limitation (spring and autumn). Overall, synthesized data suggest that climate variability is an important driver of planktonic microbes in the lagoon, both on shortterm, seasonal, and interannual time scales. Local anthropogenic impacts are apparently spatially restricted. More extensive time-series and dedicated experiments are needed to conclusively establish direct links between the dynamics of planktonic microbes and climatic and local anthropogenic alterations in the Ria Formosa Lagoon.